The Effect of Biological Organic Fertilizers on the Growth and Yield of Pagoda Mustard (Brassica narinosa) - Kakisina, Gelvin; Rehatta, Herman; Lawalata, Imelda J (Universitas Pattimura, 2023)
The use of chemical fertilizers on vegetable mustard by farmers is currently higher than the use of organic fertilizers. The use of proper organic fertilizers is an alternative to reducing the dose of chemical fertilizers to increase yields of pagoda mustard. This study aimed to determine the effect of biological organic fertilizers at various treatment doses on the growth and yield of pagoda mustard. This study was conducted in the Greenhouse of the Faculty of Agriculture, Pattimura University, from May to July 2019. It was carried out using single factor experiment in a Randomized Block Design, with biological organic fertilizer dose treatment, consisting of 6 levels: 0 ml/l, 5 ml/l, 10 ml/l, 15 ml/l, 20 ml/l, and 25 ml/l per container. The observed variables consisted of plant height, number of leaves, leaf area, crown fresh weight, root fresh weight, crown dry weight, and crown diameter. Data were analyzed statistically and further tested using Duncan's test with a level of 5%. The results showed that the treatment of biological organic fertilizers had a very significant effect on the observed variables of root fresh weight. The fertilizer dose significantly affected the observed variables of leaf number (28 and 35 days after planting, dap, ie after the plants were removed from the nursery), plant leaf area, crown fresh weight, crown dry weight, and plant crown diameter, but had no significant effect on the observed variables of plant height (14 and 21 dap) and number of leaves (14 and 21 dap).